Jurimetria como instrumento de efetividade da eficiência processual - Bilego, Renata Beatriz (2024)
Technological evolution experienced in contemporary times has transformed the activities of the Judiciary. In parallel with digital transformations, there has been an increase in the use of jurimetrics, which is the mechanism that associates the use of statistics with Law as a way of studying and understanding legal activity through data measurement. All this growth in technological development has left gaps in science that the present study aims to address, seeking to understand whether technological advances and new methods of applying the Law, through jurimetrics, contribute to the implementation of existing procedural constitutional principles, especially procedural efficiency. For this reason, the research problem aims to understand how jurimetrics can serve as an instrument to increase the effectiveness of procedural efficiency. Therefore, the objective of the research is to understand whether jurimetrics can contribute to the implementation of procedural efficiency, collaborating with the improvement of the development of activities carried out by the Judiciary, facilitating access to justice and complying with procedural constitutional principles. Thus, the bibliographic method was used in the search for results, by reviewing concepts in orderto clarify and explain the proposed theme and its relationship with fundamental rights; Explanatory research was used regarding the problem when concepts and a historical approach were carried out in detail on some topics raised in order to understand the relationship between jurimetrics, procedural constitutional principles and technological advances experienced by the Courts of Justice. Regarding the nature of the research, it was applied, since it sought to verify whether jurimetrics can assist in the implementation of procedural efficiency. Furthermore, quantitative and qualitative research was necessary regarding the performance of the jurimetric analysis developed based on data from the CNJ's Justice in number 2023. As a result, it was found that technological advances and investments in systems are notable, so much so that with the ease of access to data, the advancement of jurimetrics has been allowed, and the jurimetric research carried out has presented effective results, capable of allowing the elaboration of new measures for the exercise of its action. Thus, when the Judiciary improves its activities in order to guarantee fundamental rights, facilitating access to justice, being concerned with the reasonable duration of the process, developing maintenance and legal security measures, it can indeed be considered the materialization of the principle of procedural efficiency. Therefore, it can be concluded that jurimetrics is an auxiliary instrument for achieving procedural efficiency.